Recreational fishing in a time of rapid ocean change. (February 2017) - van Putten, Ingrid E.; Jennings, Sarah; Hobday, Alistair J.; Bustamante, Rodrigo H.; Dutra, Leo X.C.; Frusher, Stewart; Fulton, Elizabeth A.; Haward, Marcus; Plagányi, Éva; Thomas, Linda; Pecl, Gretta
Abstract: Fishing is an important recreational activity for many Australians, with one in every four people participating every year. There are however many different pressures exerted on Australian fish stocks, including climate-related changes that drive changes in local fish abundances. It is inevitable that recreational fishers will need to adapt to these changes. When resource abundance alters substantially, user adaptation to the new situation is required and policies and incentives may need to be developed to encourage behaviour change. It is important to correctly anticipate fisher's response to these policies and incentives as much as possible. Improved understanding of recreational fisher's likely adaptation decisions and the nature and timing of these decisions can help avoid unintended consequences of management decisions. Based on a survey of recreational fishers in the south-east Australian climate hotspot, we identify 4 relevant dimensions to recreational fisher's behavioural adaptation. There are differences in adaptation timing (early, late, and non-adaptors). Non-adaptors are characterised by greater cultural attachment to fishing and stronger perceptions of the factors that influence abundance change. The fisher's preferred adaptation responses and the timing of the behavioural response differs between decreasing versus increasing fish abundance. Insight into perspectives and expectations on how recreational fishers might adapt to changes is useful to develop a set of behavioural incentives that appeal to different groups but remain efficient and effective in their implementation. Such knowledge can create new pathways to achieve meaningful and targeted adaptation responses for different types of recreational fishers. Highlights: Recreational fisher's will need to adapt to climate impacts. There are differences in adaptation timing (early, late, and non-adaptors). Non-adaptors are characterised by greater cultural attachment to fishing. Timing and preferred adaptation responses differ when abundance decreases compared to when abundance increases. Implications for the design of effective communication approaches and management responses.